Influence of the environment and occupational exposure on the occurrence of Q fever - Dorko, Erik; Rimárová, Kvetoslava; Pilipčinec, Emil (Central European Journal of Public Health, 2012)
Q fever, which is caused by Coxiella bumetii, is a worldwide zoonotic infectious disease and ruminants are the main reservoir for human infections. Humans become infected primarily by inhaling aerosols that are contaminated with C. bumetii. Ingestion (particularly drinking raw milk) and person-to-person transmission are minor routes. Animals shed the bacterium in urine and faeces, and in very high concentrations in birth by-products. The bacterium persists in the environment in a resistant spore-like form which may become airborne and transported long distances by the wind. Q fever is considered primarily an occupational disease of workers in close contact with farm animals or processing their products, however, it may occur also in persons without direct contact. To prevent the introduction and spread of Q fever infection, preventive measures should be implemented including immunisation with currently available vaccines of domestic animals and humans at risk.
Keywords: zoonózy; Occupational Exposure; Occupational Diseases; zvířata; kontrola infekce; Air Pollutants, Occupational; Animals; lidé; Risk Factors; Zoonoses; bakteriální vakcíny; Livestock; látky znečišťující vzduch v pracovním prostředí; dobytek; Slovenská republika; znečištění ovzduší; Q-horečka; feces; Bacterial Vaccines; Humans; Animal Husbandry; Slovakia; chov zvířat; Feces; Air Microbiology; pracovní expozice; nemoci z povolání; rizikové faktory; mikrobiologie vzduchu; Air Pollution; Infection Control; Q Fever